Associations between prior healthcare use, time to diagnosis, and clinical outcomes in inflammatory bowel disease: a nationally representative population-based cohort study - Alex Bottle; Sonia Saxena; Richard C G Pollok; Jonathan Blackwell; Irene Petersen; Hanna Creese; Nishani Jayasooriya; Richard CG Pollok (BMJ Open Gastroenterology)
Background Timely diagnosis and treatment of inflammatory bowel disease (IBD) may improve clinical outcomes.Objective Examine associations between time to diagnosis, patterns of prior healthcare use, and clinical outcomes in IBD.Design Using the Clinical Practice Research Datalink we identified incident cases of Crohn’s disease (CD) and ulcerative colitis (UC), diagnosed between January 2003 and May 2016, with a first primary care gastrointestinal consultation during the 3-year period prior to IBD diagnosis. We used multivariable Cox regression to examine the association of primary care consultation frequency (n=1, 2, >2), annual consultation intensity, hospitalisations for gastrointestinal symptoms, and time to diagnosis with a range of key clinical outcomes following diagnosis.Results We identified 2645 incident IBD cases (CD: 782; UC: 1863). For CD, >2 consultations were associated with intestinal surgery (adjusted HR (aHR)=2.22, 95% CI 1.45 to 3.39) and subsequent CD-related hospitalisation (aHR=1.80, 95% CI 1.29 to 2.50). For UC, >2 consultations were associated with corticosteroid dependency (aHR=1.76, 95% CI 1.28 to 2.41), immunomodulator use (aHR=1.68, 95% CI 1.24 to 2.26), UC-related hospitalisation (aHR=1.43, 95% CI 1.05 to 1.95) and colectomy (aHR=2.01, 95% CI 1.22 to 3.27). For CD, hospitalisation prior to diagnosis was associated with CD-related hospitalisation (aHR=1.30, 95% CI 1.01 to 1.68) and intestinal surgery (aHR=1.71, 95% CI 1.13 to 2.58); for UC, it was associated with immunomodulator use (aHR=1.42, 95% CI 1.11 to 1.81), UC-related hospitalisation (aHR=1.36, 95% CI 1.06 to 1.95) and colectomy (aHR=1.54, 95% CI 1.01 to 2.34). For CD, consultation intensity in the year before diagnosis was associated with CD-related hospitalisation (aHR=1.19, 95% CI 1.12 to 1.28) and intestinal surgery (aHR=1.13, 95% CI 1.03 to 1.23); for UC, it was associated with corticosteroid use (aHR=1.08, 95% CI 1.04 to 1.13), corticosteroid dependency (aHR=1.05, 95% CI 1.00 to 1.11), and UC-related hospitalisation (aHR=1.12, 95% CI 1.03 to 1.21). For CD, time to diagnosis was associated with risk of CD-related hospitalisation (aHR=1.03, 95% CI 1.01 to 1.68); for UC, it was associated with reduced risk of UC-related hospitalisation (aHR=0.83, 95% CI 0.70 to 0.98) and colectomy (aHR=0.59, 95% CI 0.43 to 0.80).Conclusion Electronic records contain valuable information about patterns of healthcare use that can be used to expedite timely diagnosis and identify aggressive forms of IBD.